Starting from a blank page? Semantic similarity in central bank communication and market volatility - Michael Ehrmann; Jonathan Talmi (Bank of Canada, 2016)
Press releases announcing and explaining monetary policy decisions play a critical role in the communication strategy of central banks. Because of their market-moving potential, it is particularly important how they are drafted. Often, central banks start from the previous statement and update the earlier text with only small changes. This way, it is straightforward to compare statements and see how the central bank's thinking has evolved. This paper studies to what extent such similarity in central bank statements matters for the reception of their content in financial markets. Using the case of the Bank of Canada (the G7 central bank that had to rely the least on unconventional monetary policy following the global financial crisis and has therefore broadly continued standard monetary policy communications), the paper shows that press releases with larger differences in wording lead to higher volatility in financial markets, suggesting that their content is more difficult to absorb. At the same time, while press releases that are similar to the previous one generate less market volatility, once their wording is updated, volatility increases substantially.
Keywords: E43; E52; E58; 330; Central bank research; Financial markets; Interest rates